Drug residues assessment after extra-label use of fipronil in laying hens - Cantón, Lucila (2018)
Introduction: Current increase on Argentine poultry production is closely linked with the need of parasite control to achieve optimal production standards. However, the availability of approved antiparasitic compounds to use in poultry is scarce. Fipronil (FIP) is an insecticide belonging to the pyrazole class. FIP is authorized to control ectoparasites in small animals and cattle in some countries. It is suspected that FIP is worldwide used in an extra-label manner in poultry farming to control ectoparasites (mainly the poultry red mite Dermanyssus gallinae). A Maximum Residue Limit (MRL) (0.02 mg/kg) has been established for this molecule (sum of FIP and its sulfone metabolite, expressed as FIP) in eggs. Objective: The goal of the current study was to investigate the FIP and the FIP-sulfone metabolite residues profiles in eggs after its extra-label administration to laying hens.Materials and methods: Hens from a local farm were extralabel treated with FIP (ECTOLINE® 1%) in feed for a week. Eggs were collected for a 36 days post-treatment period. White and yolk egg samples were processed and analysed to determine FIP and FIP-sulfone metabolite residues by HPLC with diode array detection.Results and conclusions: Drug residues did not reach measurable residual concentrations in white samples after extra-label administration of FIP to laying-hens. Residual concentrations of fipronil-sulfone (active metabolite of FIP) were found in yolk egg at levels higher than those of the established MRL value. A maximum residue level (Cmax) of 2.10±0.34 µg/g was quantified at 9 days (tmax) after the beginning of treatment. Since a withdrawal period have not been established, these data strongly suggest that extra-label use of FIP could constitute a potential risk for consumers with the consequent negative economic repercussions in poultry production.